2021
DOI: 10.21037/atm-21-1540
|View full text |Cite
|
Sign up to set email alerts
|

Intraductal administration of N-methyl-N-nitrosourea as a novel rodent mammary tumor model

Abstract: Background: Chemically induced animal models of breast cancer (BC) using N-methyl-N-nitrosourea (MNU) have been widely used in preclinical research. The conventional approach entails intraperitoneal (i.p) or intravenous injection of a carcinogen, leading to tumor induction at unpredictable locations. This study aimed to establish a modified MNU-induced rat mammary tumor model using intraductal (i.duc) administration and to evaluate its biological behavior, morphology, and response to chemotherapy drugs.Methods… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 23 publications
(28 reference statements)
1
6
0
Order By: Relevance
“…During the injection, animals were maintained under anesthesia using continuous 2% isoflurane inhalation (1% oxygen). Carcinoma in situ with positive expression of ER, and negative expression of Her‐2 developed 28 to 42 days after the first intraductal injection of MNU and eventually progressed to invasive ductal carcinoma 23,43 . The animals were randomized to three groups of three to five rats each.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…During the injection, animals were maintained under anesthesia using continuous 2% isoflurane inhalation (1% oxygen). Carcinoma in situ with positive expression of ER, and negative expression of Her‐2 developed 28 to 42 days after the first intraductal injection of MNU and eventually progressed to invasive ductal carcinoma 23,43 . The animals were randomized to three groups of three to five rats each.…”
Section: Methodsmentioning
confidence: 99%
“…[24][25][26][27] In previous work, we developed the rat model by intraductal injection of MNU with a fully predictable tumor location. 23 By gene expression profiles, tumors in this model cluster with the ER-positive subtype of human BC. Likewise, the MIND model based on 4T1 cells has the advantage of presenting disease progression from DCIS to invasive carcinoma compared to the traditional fat pad model.…”
Section: Introductionmentioning
confidence: 98%
See 2 more Smart Citations
“…Long term studies have shown that some rats can develop breast tumors spontaneously (118). Use of a chemical carcinogen in rats can result in a shorter latency period to tumor development (119)(120)(121)(122)(123). Recently, 17b-estradiol (E2) was used to induce breast tumors in August Copenhagen Irish-rats by modulating estrogen mediated mechanisms in breast cancer development (121).…”
Section: Rat Bc Modelsmentioning
confidence: 99%